The Effects of Patients’ and Care-Givers’ Knowledge, Attitude, & Practice (KAP) on Quality of Life Among Thalassemia Major Patients’ in Damascus-Syrian Arab Republic - Jeesh, Yaser Adnan Abo; Yousif, Magda El-hadi Ahmad; Al-Haboub, Moauya Al-Balal (European Scientific Journal, ESJ, 2018)
Background: Thalassemia is the most common autosomal abnormality in Syria. Its complications have an important effect on education; time off school; sport; difference from friends/ siblings; social interactions; and stigmatization. Knowledge of factors associated with quality of life in thalassemia patients is necessary for forming appropriate clinical programs, social support, and improving treatment outcomes. Purpose: The study was to assess the effects of Patients’ and Care-givers’ Knowledge, Attitude, & Practice (KAP) with Quality of Life among Thalassemia Major Patients’ in Syria. Methods: Cross-sectional descriptive analytical design was conducted at the national thalassemia center in Damascus. WHOQOL-BREF and a questionnaire developed by the researcher were used to measure the participantsâ€™ knowledge, attitudes and practices of thalassemia. Results: Total of 238 thalassemia patients participated in the study. A statistical significance was found regarding improvement of skill and knowledge scores among caregivers and thalassemia patients before and after receiving the teaching guide from 12.52Â±1.77 to 14.07Â±1.01, t=11.447, p=0.000 and from 34.12Â±4.50 to 37.43Â±4.61, t=-8.58, p= .000 respectively. Stigmatization was significantly noticed among families caring for thalassemic patients. There were a significant differences in the mean score regarding nutritional status before and after teaching guide paired t test= 12.11, p= 0.000. A statistical significance was found in females regarding social domain p=0.04. However, mean scores for overall quality of life were better in females rather than males, but these mean scores were statistically insignificant p>0.05. A statistical significant difference in ferritin levels and patientâ€™s age was found. Results also revealed that no statistical significant differences was observed between overall quality of life of the four domains in relation to the two treatment groups (subcutaneous vs oral) and age groups. Conclusion: Thalassemia is a socio-economic problem. The most efficient way to reduce risks of having affected patients is by increasing the knowledge through training of parents regarding the disease. Our findings highlighted that there was lack in patientsâ€™ knowledge and skills regarding the disease, but a remarkable improvement in both knowledge and performance was found after patients received the teaching guide, which lead to an increase in overall patient’s quality of life.